Transition metal dichalcogenides composites towards high sensitivity/lower detection limit of Cu2+ ions - Loh, Felicia Yi Hui (Nanyang Technological University, 2022)
In this work, an accurate electrochemical sensor was developed for the detection of Cu2+ ions by modifying the surface of glassy carbon electrode (GCE) with vanadium selenide (VSe2) incorporated with cobalt, nickel, and titanium dopants. The doped VSe2 composites were successfully synthesised by a facile hydrothermal approach. The as-prepared VSe2 was confirmed by several analytical and spectroscopic techniques such as X-ray Diffraction (XRD), Scanning Electron Microscopy attached with Energy-Dispersive Spectroscopy (SEM-EDS), and X-ray Photoelectron Spectroscopy (XPS). The electrochemical properties and performance of Co-doped, Ni-doped, and Ti-doped VSe2 composites were investigated by performing linear sweep anodic stripping voltammetry (LSASV), and cyclic voltammetry (CV). The method was successfully applied for the detection of Cu (II) ions, and it shows the peak current increases exponentially with increasing Cu2+ concentration over the range of 10-6 mol/L to 10-2 mol/L. Among all the chemically modified working electrodes, 30% Co-doped VSe2 composite demonstrates the best performance in terms of redox potential, detection of Cu (II) ions with a detection limit of 10-6 mol/L, and reasonable stability. Also, it is evident that 30% Co-doped VSe2 composite possesses highest redox current signals, and electron transfer potential, which provides favourable properties for electrochemical sensing. In addition, it was shown that the chemically modified 30% Co-doped VSe2 composite can be applied to the quantitative determination of copper (II) ions with satisfactory results.